Milestones in the History of the Black Sea Oceanography - Kordzadze, Avtandil A.; Demetrashvili, Demuri I. (Journals of Georgian Geophysical Society, 2019)
In this paper the main stages in the history of the Black Sea oceanography are briefly described from the middle ages to the present. It is shown that modern knowledge on the Black Sea and our understanding of hydrophysical and biochemical processes of this unique sea basin is reached as a result of hard research activity of a lot of researcher-oceanographers during last centuries. Significant attention is paid to the modern operative oceanography using modern data-computing technologies and satellite remote sensing methods.